2000
DOI: 10.3923/pjbs.2000.1480.1483
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Hemoglobin gene (vgb) Transformed into Escherichia coli enhances Lead-Uptake and Minimizes it’s Adsorption

Abstract: Abstract:In Escherichia coli transformed with bacterial hemoglobin gene (vgb) has been shown to increase lead (Pb) uptake, growth yield of the cells grown in LB containing different concentration of Pb. The maximum Pb biosorption of vgb-containing and parental cells were determined to be 51 and 30.8 ppm Pb gG 1 biomass respectively. Using growth curves by liquid and solid media the inhibitory effect of Pb on parental strain was detected at lowest concentration (10 ppm). However, in vgb-containing cells, Pb wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As mentioned previously only three compounds (cupric chloride dihydrate, cupric nitrate 3 hydrate and cupric sulfate) with concentration (300 and 1000 ppm) were used in studding the profile of growth curves.The viable cells were precisely enable us to see the effect of copper compounds on the growth kinetics of the bacteria Pseudomonas aeruginosa. The bioaviability of heavy metals in the broth is more than in the plates (Khleifat and Homady, 2000). Generally the results here were in agreement with the results of biomass.…”
Section: Growth Curvessupporting
confidence: 91%
“…As mentioned previously only three compounds (cupric chloride dihydrate, cupric nitrate 3 hydrate and cupric sulfate) with concentration (300 and 1000 ppm) were used in studding the profile of growth curves.The viable cells were precisely enable us to see the effect of copper compounds on the growth kinetics of the bacteria Pseudomonas aeruginosa. The bioaviability of heavy metals in the broth is more than in the plates (Khleifat and Homady, 2000). Generally the results here were in agreement with the results of biomass.…”
Section: Growth Curvessupporting
confidence: 91%
“…13c). It was reported that optimum pH for the biodegradation of different aromatic compounds was different from one bacterium to another, for example, pH ranges between 8 and 11 for biodegradation of phenol and catechol by the bacterium Halomonas campisalis (Alva and Peyton, 2003) and for the biodegradation of phenol by Klebsiella oxytoca, the pH was 6.8 (Shawabkeh et al, 2007;(Khleifat et al, 2000;Khleifat et al, 2001;Khleifat et al, 2006;Al Qaisi et al, 2014;Aljundi et al, 2010a;Khleifat et al, 2022a;Khlaifat et al, 2019;.…”
Section: Effect Of Ph Of Culture Media On Biodegradation Of 2-cbamentioning
confidence: 99%
“…After treatment with lectin at concentrations of 15.1 g/mL to 1000 g/mL, the total biomass of the biofilm reduced depending on the concentration; treatment at 1000 g/mL showed an inhibition of more than 80%. (Khleifat et al, 2000;Khleifat et al, 2001;Khleifat et al, 2006;Aljundi et al, 2010a;Khleifat et al, 2022a;Khlaifat et al, 2019;Varijakzhan et al, 2021a). It was discovered, however, that some of the marine sponge chemicals were less efficient against Gram-negative bacteria.…”
Section: Antibacterial Activity Of Various Compounds Isolated From Ma...mentioning
confidence: 99%